Plastics piping systems for drainage, sewerage and water supply, pressure and non-pressure. Glass-reinforced thermosetting plastics (GRP) based on unsaturated polyester resin (UP). Guidance for the assessment of conformity. (30th June 2023) - British Standards Institution,
No abstract available